2013
DOI: 10.1111/jop.12074
|View full text |Cite
|
Sign up to set email alerts
|

High expression of p63 is correlated to poor prognosis in squamous cell carcinoma of the tongue

Abstract: Based on the present data, we recommend using expression of p63 as an additional factor contributing prognostic information in analysis of SCC in the tongue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
0
14
1
1
Order By: Relevance
“…Although some studies had reported an influence of p63 expression in clinical–pathological characteristics (Lo Muzio et al , ; de Oliveira et al , ; Moergel et al , ; Loljung et al , ), we could not find any relationship of p63 with these parameters in our sample. This was true even on survival analysis.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…Although some studies had reported an influence of p63 expression in clinical–pathological characteristics (Lo Muzio et al , ; de Oliveira et al , ; Moergel et al , ; Loljung et al , ), we could not find any relationship of p63 with these parameters in our sample. This was true even on survival analysis.…”
Section: Discussioncontrasting
confidence: 75%
“…This was true even on survival analysis. This result is not unexpected as many studies had reported conflicting results on p63 expression in survival analysis using IHC (Lo Muzio et al , ; de Oliveira et al , ; Moergel et al , ; Loljung et al , ). These discrepancies could be related to the different functions of p63 isoforms perhaps in different tumours locations.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The dysregulation of TP63 has been reported in various human malignancies and its overexpression is closely associated with clinical outcomes [18, 19, 37, 38]. Generally, OSCC patients with elevated TP63 levels have a poorer survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have documented a link between the aberrant expression of TAp63 (22) and the pathogenesis/prognosis in several types of cancer (23,24). However, thus far, the expression and clinical significance of TAp63 in colorectal cancer (CRC) have not been explored.…”
Section: Discussionmentioning
confidence: 99%